Lanthanum Hydroxychloride/Anatase Composite and Its Application for Effective Uv-Light Driven Oxidation of the Emergent Water Contaminant Cetirizine - Venegas-Yazigi, D; Venegas-Yazigi, D; Soto-Donoso, N; Soto-Donoso, N (Institution of Chemical Engineers, 2023)
This work reports on the successful synthesis of a new composite named TiO2@La(OH)2Cl using a sol-gel and hydrothermal route. This method is considered an inexpensive and environmentally friendly synthetic method to produce materials with controllable size and morphology. A combination of X-Ray powder diffraction, X-Ray photoelectron spectrometry and Scanning Electron Microscopy revealed that the composite is made of micrometric platelets of La(OH)2Cl covered by c.a. 10 nm TiO2 anatase nanoparticles. The activity in photocatalytic reactions was examined through cetirizine degradation under UV-A irradiation. Results of the screening studies confirmed the excellent photocatalytic activity of the as-synthesized composite compared to pure anatase and pure La(OH)2Cl, highlighting the positive role of the synergy between the two solids. The composite was further explored in detail in terms of catalyst load, pollutant concentration, water matrix and mechanism of the reaction. The target molecule was completely removed from the aqueous suspension at 2.5 mg/L of pollutant and 0.2 g/L of catalyst load. Also, reaction mechanism evaluation showed the active role of hydroxyl radicals in the degradation of cetirizine by the TiO2@La(OH)2Cl composite. Additionally, phytotoxicity investigations were performed to study the germination of cress seeds for treated and raw solutions. Data revealed that the degradation reaction products for cetirizine were scarcely toxic compared to the untreated sample confirming the usefulness of the photocatalytic treatment with the TiO2@La(OH)2Cl composite. Lastly, all these data demonstrate the excellent catalytic efficiency of the new synthesized material, opening new ways for its use for future applications for water purification. © 2023 Institution of Chemical Engineers